L’apprentissage de l’ergonomie demande un nouveau regard : le cas d’un programme de spécialisation au Brésil - Laerte Sznelwar; Fausto Mascia; Leila Zidan; Flora Vezzá (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper describes reflection on the learning process of adults who are studying in an ergonomics specialization program. The main questions raised here relate to the difficulties these students face in their theoretical and practical learning of Ergonomic Work Analysis, as well as ergonomic concepts. Some of the points discussed are the students’ initial training, the social relationships established during their practical work, and the relationship to uncertainty, an important characteristic linked to the complexity of this approach.